2014
DOI: 10.1002/prep.201400154
|View full text |Cite
|
Sign up to set email alerts
|

Compacted Modified Propellant Blocks as Traveling Charge in the Hybrid Shot Scheme

Abstract: The burning of compacted modified propellant charges applied as a traveling charge in the hybrid shot scheme was studied. The block charges were manufactured by pressing fine propellant grains coated by a thin film of polyvinyl butyral. A stick from several pressed pellets was insulated over its lateral surface by a thin layer of silicon paste, glued to the back of the projectile and inserted into the barrel of the 23‐mm smooth‐bore laboratory gun. The loose‐packed accelerator charge was placed in the breech. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Some of these parameters are listed in Table 1 and have been derived from various test methods. The Trauzl lead-block test measures the deformation induced by 10 g of explosive in a standardised lead block as a means to compare performance [139,140] High speed camera photography is used frequently to image burn and propagation rate, size of emitted particles or ionised gas, and ignition delay (also measured by oscilloscope) [56,141]. Figure 13 shows snap shots of a typical plasma formation sequence after application of a 420 V bias to a metallic bridge.…”
Section: Characterisation: Techniques and Principlesmentioning
confidence: 99%
“…Some of these parameters are listed in Table 1 and have been derived from various test methods. The Trauzl lead-block test measures the deformation induced by 10 g of explosive in a standardised lead block as a means to compare performance [139,140] High speed camera photography is used frequently to image burn and propagation rate, size of emitted particles or ionised gas, and ignition delay (also measured by oscilloscope) [56,141]. Figure 13 shows snap shots of a typical plasma formation sequence after application of a 420 V bias to a metallic bridge.…”
Section: Characterisation: Techniques and Principlesmentioning
confidence: 99%
“…Scholars at home and abroad have studied the properties of propellants for decades and achieved remarkable results. Khomenko Yu P [1],Ermolaev B S [2][3][4] researched on using porous ring-cut rod propellant charging technology to improve the loading density, the maximum filling density reaches more than 1.1g/cm 3 , and the filling density can be increased by more than 10% compared with the granular propellant charge. Through the selection of binders, plasticizers and combustion modifiers for lowsusceptibility emissions, as well as the design and theoretical calculation of formulas and theoretical calculations, Liao Xin [5,6] basically determined the formulation of the low vulnerability propellant composed of RDX as energy-containing fillers, inert energetic composite binder, composite plasticizer, combustion modifier and mechanical property improvers.…”
Section: Introductionmentioning
confidence: 99%
“…The test results showed that the projectile muzzle velocity could be increased by 2.8% and 4.2% respectively under the maximum chamber pressure of 330MPa and 400MPa with the traveling charge scheme covered by flame retardants. In 2014, Ermolaev B S et al [16] made an traveling charge by bonding and compacting fine propellant grains and covering them with polyvinyl butyral diaphragm, which was glued to the bottom of the projectile by silicone rubber, and carried out an experimental study using a 23 mm smoothbore ballistic gun, which showed that the use of this compacted block as an traveling charge provided a stable combustion process, which resulted in an increase in the projectile muzzle velocity by about 20%. In 2015, Michaels D et al [17] from Israel studied a propulsion system based on combustion chamber jet traveling charge and established an interior ballistic model, which was compared and verified with the test results.…”
Section: Introductionmentioning
confidence: 99%